THE INFLUENCE OF READING BOOKS IN A FOREIGN LANGUAGE ON THE WORLDVIEW OF CHILDREN - Tagayeva Svetlana; Bozorboyeva Iroda; Redjepova Aynura (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: Reading foreign language books is an important factor in shaping children’s outlook. This article emphasizes the importance of this process and reflects on how foreign language literature affects the development of empathy, cultural awareness and creativity in children. foreign language books are invaluable in preparing the young generation for global citizenship. Age-appropriate books provided by parents and educators encourage children not only to learn a new language, but also to understand other cultures. This process not only increases children’s academic knowledge, but also has a positive effect on their social and emotional development.